Exploring the inhibitory potential of bioactive compound from Luffa acutangula against NF-κB—A molecular docking and dynamics approach. (June 2016) - Ramar, Vanajothi; Pappu, Srinivasan
Graphical abstract: Highlights: NF-κB signaling is a major target for anticancer drug development. Bioactive compound was isolated form Indian traditional medicinal plant L. acutangula . The binding affinity of isolated bioactive compound and NF-κB was investigated by in silico approach. Abstract: Nuclear factor kappa B (NF-κB) is a transcription factor, plays a crucial role in the regulation of various physiological processes such as differentiation, cell proliferation and apoptosis. It also coordinates the expression of various soluble proinflammatory mediators like cytokines and chemokines. The 1, 8-dihydroxy-4-methylanthracene-9, 10-dione (DHMA) was isolated from Luffa acutangala and its in vitro cytotoxic activity against NCI-H460 cells was reported earlier. It also effectively induces apoptosis through suppressing the expression NF-κB protein. Based on experimental evidence, the binding affinity of compound 1 with NF-κB p50 (monomer) and NF-κB-DNA was investigated using molecular docking and its stability was confirmed through molecular dynamic simulation. The reactivity of the compound was evaluated using density functional theory (DFT) calculation. From the docking results, we noticed that the hydroxyl group of DHMA forms hydrogen bond interactions with polar and negatively charged amino acid Tyr57 and Asp239 and the protein-ligand complex was stabilized through pi-pi stacking with the help of polar amino acid His114, which plays a key role in binding of NF-κB to DNA at a site of DNA-binding region (DBR). The result indicates that the isolated bioactive compound DHMA might have altered the binding affinity between DNA and NF-κB. These findings suggest that potential use of DHMA in cancer chemoprevention and therapeutics.